Ambiguitas dan Diferensiasi Agama dan Negara di Indonesia - Binsar Antoni Hutabarat (Reformed Center for Religion and Society, 2018)
ABSTRACT:This article entitled, The Ambiguity of the Differentiation between Religion and Nation in Indonesia focuses on discussing how the relationship between religion and nation is not subduing one another. First of all, it is discussed about the latest research on the relationship between religion and nation, and its theoretical basis as the foundation, then the theory of differentiation between religion and nation also discussed as the best middle way of the relationship between religion and nation that is not subduing one another. After that, it is also discussed about the concept of differentiation between religion and nation according to Pancasila, and the ambiguity happened towards the policy of differentiation between religion and nation in Indonesia. In this writing, it is found that the differentiation between religion and nation according to Pancasila has a strong theoretical basis and relevant in Indonesian context. It is only that the impact of the ambiguity of differentiation still causes discriminative action to certain religion.Â KEYWORDS:ambiguity, differentiation, religion and nation, Pancasila